2003
DOI: 10.1097/01.tp.0000053755.08825.12
|View full text |Cite
|
Sign up to set email alerts
|

Accurate preoperative estimation of liver-graft volumetry using three-dimensional computed tomography

Abstract: Three-dimensional CT volumetry is useful for size matching in cases of living-related orthotopic liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
127
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 11 publications
1
127
1
3
Order By: Relevance
“…The remnant liver must therefore be able to overcome the necrosis, preserving or recovering an adequate synthetic ability [22] ; as a consequence, there must be an adequate and functional FLRV to avoid PHLF [23] . Despite this, there is no uniform consensus among hepatic surgeons on the amount of liver volume that can be safely resected, with a wide range of reported values [24,25] . Guglielmi et al [24] reported that in patients with "healthy" liver (absence of hepatic diffuse disease, normal functionality tests) the limit of FLRV% for a safe resection varies between 20% and 30%, while in patients with underlying hepatic disease (cirrhosis, cholestasis, steatosis) the critical FLRV% value rise up to 30%-40%.…”
Section: Introductionmentioning
confidence: 99%
“…The remnant liver must therefore be able to overcome the necrosis, preserving or recovering an adequate synthetic ability [22] ; as a consequence, there must be an adequate and functional FLRV to avoid PHLF [23] . Despite this, there is no uniform consensus among hepatic surgeons on the amount of liver volume that can be safely resected, with a wide range of reported values [24,25] . Guglielmi et al [24] reported that in patients with "healthy" liver (absence of hepatic diffuse disease, normal functionality tests) the limit of FLRV% for a safe resection varies between 20% and 30%, while in patients with underlying hepatic disease (cirrhosis, cholestasis, steatosis) the critical FLRV% value rise up to 30%-40%.…”
Section: Introductionmentioning
confidence: 99%
“…Among the suggested causes of errors in estimating liver volume by volumetric CT are partial volume effects, examination technique, hepatic physical density, exact contour and segment recognition, intraoperative drainage of liquid from the liver, and hepatic volume variation. 7,9,10,30 It is likely that blood volume contributes a significant portion of the error because this volume is included in CT volumetry, whereas graft weight is generally measured in a blood-free manner. 31 In the present study, however, we used a blood-free CT technique for all subjects to minimize the effects of blood volume and maximize those of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] In addition, CT volume measurements have been shown to be well-correlated with the values calculated by various numerical formulas for liver weight/volume combining parameters, such as body weight, height, and body surface area. 7,8,11 Thus, CT volumetry is widely used for estimating liver volume. 12 Because human fat has a density of 0.9 g/cm³ and contains less functional mass (g) than normal liver per unit volume (cm³), there is a possibility of error in estimating liver mass by CT volumetry in patients with hepatic steatosis, especially in severe cases.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to preceding research, Hiroshige et al, reported that it is important to understand the anatomical structure of blood vessels in the liver and bile duct in the donors and recipients accurately before transplantation through imaging screening for the donors' safety and the prevention of liver dysfunction after the transplantation [11]. MRCP technology has improved since it was first known by Dooms et al In 1986, and currently, MRCP is used to provide quality diagnostic images for the pancreaticobiliary duct by imaging the bile in the pancreaticobiliary duct with high signal intensity.…”
Section: Discussionmentioning
confidence: 99%